2016
DOI: 10.5152/kd.2016.02
|View full text |Cite
|
Sign up to set email alerts
|

Crimean-Congo Haemorrhagic Fever: Treatment and Use of Ribavirin

Abstract: Crimean-Congo haemorrhagic fever

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…In our study, the physical examination findings included fevers, headaches, weakness, and diffuse muscular and articular pain. Thrombocytopenia (95.8%) and leukopenia (87.5%) were the most common laboratory findings, consistent with the literature [11,17,21]. All the patients included in our study recovered, and no mortality occurred following discharge.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the physical examination findings included fevers, headaches, weakness, and diffuse muscular and articular pain. Thrombocytopenia (95.8%) and leukopenia (87.5%) were the most common laboratory findings, consistent with the literature [11,17,21]. All the patients included in our study recovered, and no mortality occurred following discharge.…”
Section: Discussionsupporting
confidence: 90%
“…However, field studies conducted in Turkey since 2005 have shown that the main tick species responsible for CCHF epidemics was Hyalomma marginatum. The CCHF virus has the most common geographic distribution among tick-borne viruses [1,[4][5][6].…”
mentioning
confidence: 99%